Coconut Growers' Knowledge and Perceptions on Climate Change and Adaptation Strategies in Puttalam District of Sri Lanka - Gajanayake, Bandara; Godage, Ruvani Subhathma Wickramarathna (International Coconut Community Journal, 2022)
ABSTRACT At present climate changes and extreme weather events which are significantly affects the productivity of coconut in the major coconut growing areas in the country and ultimately it will threaten the livelihood of coconut cultivating community. The present study was undertaken to determine the coconut growers’ knowledge and perceptions about climate change and adaptation strategies. The study was conducted in Puttalam district which is more vulnerable to climate change impacts. The study sample comprised of 140 coconut growers. The study findings emphasized that notable fraction of growers have fairly high knowledge and perceptions about climate change and various impacts. Further, age, education and farming experience were found to be positively related and gender, land holding, family size, land ownership were negatively related with growers’ knowledge and perceptions. Additionally, age, family size and education were found to be significantly related with growers’ knowledge and only the family size and education were found to be significantly related with growers’ perceptions. Moreover, growers’ knowledge was positively and significantly related with their perceptions and adaptation measures as well as perceptions also positively and significantly related with adaptation measures. Also, findings showed that significant importance to create extension and awareness campaigns to educate the coconut growers about climate change related risks and uncertainties and suitable adaptation strategies. Therefore, agriculture policy makers should more focus on mitigating impacts of climate change to enhance the sustainable coconut cultivation in the country with providing more information, financial supports and subsidies to growers to adopt suitable adaptation measures. Keywords: adaptation strategies, climate change, coconut growers’ knowledge, perceptions